Imagination Book - Shaheen, Aya; Salawdeh, Amal (My University, 2017)
Picture books are not meant only for children some are aimed at adults. But what about a living 3D picture book where you can play inside the story with its characters? Having fun and learn while mixing real world with digital world using Augmented Reality. Children now a day tend to play with personal electronic devices rather than reading a book. Imagination Book try to solve this problem. It is full of challenges and many cards aimed to entertain the player and make him excited to know the challenge each card in the game contains. Solving challenges and gaining the necessary amount of points will enable the player to move on to the next level. Also, it will help player to learn some skills. Such as differentiate between geometric shapes. Also aid our children to focus and concentrate at simple details in order to learn challenge and attention that lead to successful result, at same time enjoy entertainment time by mixing real with virtual world. To build the project, we will use Unity 3D game engine and Vuforia AR SDK for Android devices.